LaserWriter II : a novel - Shopsin, Tamara (MCD / Farrar, Straus and Giroux, 2021)
"From the incomparable New York Times and New Yorker illustrator Tamara Shopsin, a debut novel about a NYC printer repair technician who comes of age alongside the Apple computer-featuring original artistic designs by the author"--